Targeting the Wnt/β-Catenin Signaling Pathway as a Potential Therapeutic Strategy in Renal Tubulointerstitial Fibrosis - Li, Shan-Shan; Sun, Qian; Hua, Meng-Ru; Suo, Ping; Chen, Jia-Rong; Yu, Xiao-Yong; Zhao, Ying-Yong (Frontiers in Pharmacology, 2021)
The Wnt/β-catenin signaling pathway plays important roles in embryonic development and tissue homeostasis. Wnt signaling is induced, and β-catenin is activated, associated with the development and progression of renal fibrosis. Wnt/β-catenin controls the expression of various downstream mediators such as snail1, twist, matrix metalloproteinase-7, plasminogen activator inhibitor-1, transient receptor potential canonical 6, and renin-angiotensin system components in epithelial cells, fibroblast, and macrophages. In addition, Wnt/β-catenin is usually intertwined with other signaling pathways to promote renal interstitial fibrosis. Actually, given the crucial of Wnt/β-catenin signaling in renal fibrogenesis, blocking this signaling may benefit renal interstitial fibrosis. There are several antagonists of Wnt signaling that negatively control Wnt activation, and these include soluble Fzd-related proteins, the family of Dickkopf 1 proteins, Klotho and Wnt inhibitory factor-1. Furthermore, numerous emerging small-molecule β-catenin inhibitors cannot be ignored to prevent and treat renal fibrosis. Moreover, we reviewed the knowledge focusing on anti-fibrotic effects of natural products commonly used in kidney disease by inhibiting the Wnt/β-catenin signaling pathway. Therefore, in this review, we summarize recent advances in the regulation, downstream targets, role, and mechanisms of Wnt/β-catenin signaling in renal fibrosis pathogenesis. We also discuss the therapeutic potential of targeting this pathway to treat renal fibrosis; this may shed new insights into effective treatment strategies to prevent and treat renal fibrosis.